Inhibition of GH3 and HEK293 pituitary adenoma cell growth by Trigonella foenum-graecum extract (TFGE) via mTORC1 down-regulation. Issue 1 (1st January 2021) - Wang, Jing; Li, Wencong; Chen, Xingwang
Abstract : The present study investigated the effect of Trigonella foenum-graecum extract (TFGE) on GH3 and HEK293 pituitary adenoma cell growth in vitro in mice model in vivo and evaluated the underlying mechanism. TFGE exposure in dose-dependent manner suppressed the viability of GH3 and HP75 cells at 5–30 µM concentrations. Treatment of GH3 and HP75 cells with 30 µM TFGE inhibited colony formation significantly ( P  < .05) compared to the un-exposed cells. In GH3 and HP75 cells, TFGE exposure suppressed invasion potential significantly ( P  < .05) at 5 and 30 µM concentrations. TFGE treatment at 5 and 30 µM for 72 h significantly ( P  < .05) elevated induction of apoptosis. The H19 expression was significantly ( P  < .05) inhibited by TFGE-treatment in GH3 and HEK293 cells. TFGE treatment at 2.5 and 10 mg/kg doses led to a significantly ( P  < .05) suppression in the tumor growth in HP75 cell-implanted mice. TFGE treatment of GH3 and HP75 cells at 5 and 30 µM down-regulated 4E-BP1 activation. TFGE treatment inhibits GH3 and HEK293 cell viability and inhibits tumor development. It suppresses H19 expression and upregulates 4E-BP1 phosphorylation in GH3 and HEK293 cells. Therefore, TFGE may be used for the treatment of pituitary adenoma.